Biochemical exploration of β-lactamase inhibitors - Arer, Varshaa; Kar, Debasish (Frontiers in Genetics, 2023)
The alarming rise of microbial resistance to antibiotics has severely limited the efficacy of current treatment options. Prevalence of β-lactamase enzymes is a significant contributor to the emergence of resistance to antibiotics. There are four classes of β-lactamases: class A, class B, class C, and class D. Class B is the metallo-β-lactamase, while the rest of the classes are serine β-lactamases. Clinical use of β-lactamase inhibitors began as an attempt to combat β-lactamase-mediated resistance. Although β-lactamase inhibitors alone are ineffective against bacteria, research has shown that combining inhibitors with antibiotics is a safe and effective treatment that not only prevents β-lactamase formation but also broadens the range of activity. These inhibitors may cause either temporary or permanent inhibition. The development of new β-lactamase inhibitors will be a primary focus of future research. Recent advances in the knowledge of the biochemistry behind β-lactam breakdown are discussed, with a special emphasis on the mechanism of inhibitors for β-lactam complexes with β-lactamase. Secondly, focusing on the pharmacokinetic and pharmacodynamic properties of all inhibitors, and lastly, applying them in clinical settings. Our analysis and discussion of the challenges that exist in designing inhibitors might help pharmaceutical researchers address the root cause and develop more effective inhibitors.